Rencana Pengembangan Pertanian Apel Dengan Pendekatan Community Based Development (Studi di Desa Poncokusumo Kecamatan Poncokusumo Kabupaten Malang) - Rif'an Zamhari (Jurnal Administrasi Publik, 2016)
Abstract: Planing of The Apple Agriculture Development with Community Based Development Approach (The studies in Poncokusumo Village, Poncokusumo, Malang). The development of apple agriculture in Poncokusumo recently, tends to be not advocacy to those farmer communities. Determinant parties in the development so far are the Regent and SKPD related, while the farm community development only affected parties. Therefore, the development of apple agriculture model that emphasizes the importance of community-based development is needed. To aim that, the planning of the development of apple agriculture in farmer communities in Poncokusumo is needed. Development planning for the next 5 years development plan consists of 5 sub-systems of agriculture; (a) provision of means of production, prepare agricultural infrastructures. (b) On-farm, coaching and development of farming through apprenticeship to increase apple production. (c) Off-farm, post-harvest handling to advanced treatment. (d) Marketing, marketing of farming and processing through trading agencies apples. (e) Supporting, all activities which serve to optimize the performance of the four sub-systems before. Comprehensively the draft planing of Poncokusumo’s apple farm requires the development of technology-based economy of agriculture with farming communities as actors to make a community based on development. Keywords: planning, apple, community based development Abstrak: Rencana Pengembangan Pertanian Apel dengan Pendekatan Community Based Development (Studi di Desa Poncokusumo Kecamatan Poncokusumo Kabupaten Malang). Pengembangan pertanian apel selama ini di Desa Poncokusumo cenderung tidak memberikan peran kepada masyarakat tani. Pihak penentu dalam pengembangan selama ini adalah Bupati dan SKPD terkait, sedangkan masyarakat tani hanya pihak terkena dampak pengembangan. Oleh karenanya dibutuhkan model pengembangan pertanian apel yang menekankan pentingnya pengembangan berbasis masyarakat. Untuk mewujudkannya maka dibutuhkan rencana pengembangan pertanian apel. Rencana pengembangan untuk 5 tahun ke depan terdiri dari 5 rencana pengembangan sub sistem pertanian; (a) penyediaan sarana produksi, mempersiapkan infrastuktur pertanian. (b) On farm/usahatani, pembinaan dan pengembangan usahatani melalui permagangan untuk meningkatkan produksi apel. (c) Off farm/pengolahan hasil, penanganan pasca panen hingga pengolahan lanjutan. (d) Pemasaran, pemasaran hasil usahatani dan pengolahan melalui lembaga trading apel. (e) Penunjang, seluruh kegiatan yang berfungsi untuk mengoptimalkan kinerja keempat sub sistem sebelumnya. Secara komprehensif rancangan pengembangan pertanian apel Desa Poncokusumo menghendaki perekonomian berbasis teknologi pertanian dengan masyarakat tani sebagai aktornya untuk mewujudkan community based development. Kata kunci: rencana, apel, community based development